Multiple aspects of male germ cell development and interactions with Sertoli cells require inositol hexakisphosphate kinase-1 - Chenglai Fu (Nature Portfolio, 2018)
Abstract Inositol hexakisphosphate kinase-1 (IP6K1) is required for male fertility, but the underlying mechanisms have been elusive. Here, we report that IP6K1 is required for multiple aspects of male germ cell development. This development requires selective interactions between germ cells and Sertoli cells, namely apical ectoplasmic specialization. Spermiation (sperm release) requires tubulobulbar complexes. We found that the apical ectoplasmic specialization and tubulobulbar complexes were poorly formed or disrupted in IP6K1 KOs. Deletion of IP6K1 elicited several aberrations, including: 1, sloughing off of round germ cells; 2, disorientation and malformation of elongating/elongated spermatids; 3, degeneration of acrosomes; 4, defects in germ-Sertoli cell interactions and 5, failure of spermiation. Eventually the sperm cells were not released but phagocytosed by Sertoli cells leading to an absence of sperm in the epididymis.